Nitric oxide induces apoptosis in a human colonic epithelial cell line, T84 - M. Sandoval; X. Liu; P. D. Oliver; X.-J. Zhang; D. A. Clark; M. J. S. Miller (Hindawi Limited, 1995)
Chronic inflammation is associated with inducible nitric oxide synthase expression in infiltrating and resident cells (epithelia, neurons) and an exaggerated release of nitric oxide. NO can induce apoptosis in macrophages and tumour cell lines. We investigated whether NO induced cell death in an epithelial (T84) cell fine via apoptosis. Culture T84 cells were exposed to a bolus of NO (40 or 80 μM) dissolved in Hank's balanced salt solution (HBSS) supplemented with 10% fetal calf serum (FCS). After incubation for 4 h at 37°C in 5% CO2, cells were either stained for DNA fragmentation with the TdT-mediated dUTP-biotin nick end labelling (TUNEL) method, or cytosolic DNA fragments quantified by a cell death detection ELISA assay. Nitric oxide induced apoptosis in a dose-dependent manner which preceded frank cell death (failure to exclude Trypan blue). These data suggest that epithelial cell death may be NO dependent and via apoptosis, in states of gut inflammation.